X-ray diffraction study of evaporated cadmium telluride thin films - Ismail, Bakar (Faculty of Science, 2009)
X-ray diffraction measurement was performed on evaporated CdTe thin films indicating a preferential orientation in (111) direction. The effect of the deposition rate, thickness and substrate temperature was investigated and the film quality was discussed. It was found that as the deposition rate was increased finer crystallite size was obtained, while at the same time the micro-strain decreased. The decrease in crystallite size at higher deposition rate can be interpreted according to the increased velocity and intensity of the vapour atoms during rapid film formation. The crystallite size increased as the substrate temperature was increased up to 200 oC, above which the crystallite size decreased again. As the thickness was increased the micro-strain decreased, while the crystallite size increased with thickness